2019
DOI: 10.1016/j.tsf.2019.137492
|View full text |Cite
|
Sign up to set email alerts
|

Optical optimization of semi-transparent a-Si:H solar cells for photobioreactor application

Abstract: To improve the overall photoconversion efficiency and provide energy support for microalgae culture, we propose to develop a photobioreactor (PBR) and 2 photovoltaic technology (PV) coupled system using a-Si:H solar cells directly placed on the PBR's illuminated surface. PV cells have to absorb a part of the incident light to produce electricity while being transparent in the photosynthesis wavelength range. Growing test of Phaeodactylum Tricornutum shows that PV optical filtering does not influence the growth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 28 publications
0
4
0
Order By: Relevance
“…[1][2][3][4][5] Other novel applications include agrophotovoltaics (APV) and application as devices that could be integrated as functional components to power mid and low power optoelectronic devices such as sensors, electrochromic windows, as a multifunctional harvester and optical filter, as indoor light harvesters or Internet of Things devices. [6][7][8][9][10][11] For transparent PV applications maximal efficiency is not the key premise for massive deployment. Instead, other aspects such as visual impact, low cost, and stability play an important role in their viability.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3][4][5] Other novel applications include agrophotovoltaics (APV) and application as devices that could be integrated as functional components to power mid and low power optoelectronic devices such as sensors, electrochromic windows, as a multifunctional harvester and optical filter, as indoor light harvesters or Internet of Things devices. [6][7][8][9][10][11] For transparent PV applications maximal efficiency is not the key premise for massive deployment. Instead, other aspects such as visual impact, low cost, and stability play an important role in their viability.…”
Section: Introductionmentioning
confidence: 99%
“…[ 1–5 ] Other novel applications include agrophotovoltaics (APV) and application as devices that could be integrated as functional components to power mid and low power optoelectronic devices such as sensors, electrochromic windows, as a multifunctional harvester and optical filter, as indoor light harvesters or Internet of Things devices. [ 6–11 ]…”
Section: Introductionmentioning
confidence: 99%
“…6 Recently, the filtering effect of a semitransparent hydrogenated amorphous silicon-based solar cell was also proposed. 13 Optical modifications of thin solar cell layer thicknesses and reactive ion etching of the glass substrate helped maintain a high PV efficiency, while maintaining the growth rate of the microalgae growing test of Phaeodactylum tricornutum.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Another study relying on the same principle of using spectrally selective photovoltaic cells demonstrated the possibility of producing 20.3 g m 2 /day of algal biomass and 0.22 kW h m 2 /day of electricity by utilizing multiple band gaps in a single system under an illumination of 7.2 kW h m 2 /day . Recently, the filtering effect of a semitransparent hydrogenated amorphous silicon-based solar cell was also proposed . Optical modifications of thin solar cell layer thicknesses and reactive ion etching of the glass substrate helped maintain a high PV efficiency, while maintaining the growth rate of the microalgae growing test of Phaeodactylum tricornutum.…”
Section: Introductionmentioning
confidence: 99%